2009
DOI: 10.1143/jjap.48.06fe01
|View full text |Cite
|
Sign up to set email alerts
|

Graphite Shell Film Formation Induced by Eduction Phenomenon of Ga Implanted by Focused Ion Beam

Abstract: In this study, we used a transmission electron microscope (TEM) to evaluate the structure of the gallium (Ga) sphere formed on the tip of a diamond-like carbon (DLC) pillar fabricated by focused-ion-beam chemical vapor deposition (FIB-CVD). Until now, details of the phenomenon induced by Ga eduction were remained unclear. We found that a graphite shell was formed on the surface of the Ga sphere after annealing. In addition, we demonstrated that this graphite shell film could be separated from the Ga sphere by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In contrast with previous in situ TEM observations, we do not observe graphitic shell formation around the droplets. 19,21,22,24 We do, however, observe small remnants that do not change in size after the bulk of the droplets dissolve. While the images lack sufficient resolution to identify these features, presumably they are graphitic shells as has been reported in the literature.…”
mentioning
confidence: 52%
See 3 more Smart Citations
“…In contrast with previous in situ TEM observations, we do not observe graphitic shell formation around the droplets. 19,21,22,24 We do, however, observe small remnants that do not change in size after the bulk of the droplets dissolve. While the images lack sufficient resolution to identify these features, presumably they are graphitic shells as has been reported in the literature.…”
mentioning
confidence: 52%
“…While carbon is expected to be insoluble in liquid gallium, previous studies have suggested otherwise and due to the large difference in the surface energies, liquid gallium does not wet amorphous carbon and forms droplets with wetting angles exceeding 120 . 19,[21][22][23] In this letter, we present in situ transmission electron microscopy (TEM) studies of the decay behavior of Ga droplets on amorphous carbon thin films during annealing. From the time-lapsed TEM images, we find that smaller droplets shrink and the volume decay rates depend on the local environment, characteristic of surface-diffusion-limited Ostwald ripening.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The increase to the peak value at 200 ºC may be due to Ga-Si structural change by annealing. Ga evaporation during annealing at more than 400 ºC causes decrease of Young's modulus [6]. The slight increase between 600 ºC to 1000 ºC suggests Si-H/Si-O ratio change.…”
Section: Evaluation Of Mechanical Propertiesmentioning
confidence: 99%